Peran Orang tua dan Guru dalam Menejemen Sarana dan Prasrana untuk Mendukung Meningkatan Mutu Pendidikan di MI NW Keruak - Nasrullah (Pendidikan Al-Gafari, 2024)
Facilities and infrastructure are an important part of education. Educational facilities are all directly used in the teaching and learning process so that the education objectives can run smoothly and achieve their goals. This study was conducted to determine 1) the role of parents and teachers in the management of facilities and infrastructure at MI NW Keruak and 2) the management of facilities and infrastructure to support the improvement of the quality of education at MI NW Keruak. This type of research is qualitative descriptive while the method used in this study to analyze the problem is descriptive with a case study. The data collection technique uses observation, interview, and documentation methods, then processed with descriptive analysis to describe each data obtained. In this study the author uses data analysis based on the data received and then develops and concludes, the steps are data reduction, triangulation, data presentation, and verification/conclusion. Based on the data analysis, it can be explained that overall even though MI NW Keruak still has inadequate facilities such as classes and supporting media for the learning process such as infocus, in general, it has supported the teaching and learning process. In looking at the role of parents or guardians and teachers in the management of facilities and infrastructure at MI NW Keruak, it can be seen from several processes, namely the planning process, procurement process, and maintenance process. The role of parents or guardians is more towards the planning process and procurement process. The role of teachers is in the three processes, namely the planning process, procurement, and maintenance. Management of facilities and infrastructure to support improving the quality of education at MI NW Keruak includes the following processes: planning, procurement, use and maintenance, inventory, and disposal in detail.